(untitled) (icade. Journal of the Faculty of Law at Universidad Pontificia Comillas, 2016)
The teachings of the Catholic Church about business ethics are centred on the orientation of business towards persons and the common good. Business enterprise is understood as a community of persons, who, within this community, have the possibility to develop themselves by serving society through providing goods and services. The purpose of the business enterprise is to maintain itself as a community which carries out this mission of service. Thus profits are important but they are not the supreme end of a business. Considering work and its organization, consumerism and commercial transactions, people are primary, and never can be reduced to an instrument for production or an object of consumption. Rights of persons ought to be respected. Managers and entrepreneurs have to assume their social responsibility and try to live Christian virtues within business.